OP0205 April induces a novel subset of iga+ regulatory b cells that suppress inflammation through the expression of il-10 and pd-l1. (12th June 2018) - Fehres, C.; van Uden, N.; Yeremenko, N.; Fernandez, L.; Franco Salinas, G.; van Duivenvoorde, L.; Huard, B.; Morel, J.; Spits, H.; Hahne, M.; Baeten, D.
Abstract : Background: Regulatory B cells (Bregs) are immunosuppressive cells that modulate immune responses through multiple mechanisms, such as the production of IL-10 and the skewing of T cell differentiation in favour of a regulatory phenotype. However, the signals required for the differentiation and activation of these cells remain still poorly understood. We have already shown that overexpression of the TNF family member A PRoliferation-Inducing Ligand (APRIL) reduces the incidence and severity of collagen-induced arthritis (CIA) in mice. Objectives: As we have also found that APRIL promoted IL-10 production and regulatory functions in human B cells, we hypothesised that APRIL, but not BAFF, may be involved in the induction and/or activation of IL-10 producing Bregs that suppress inflammatory responses in vitro and in vivo . Methods: Peripheral blood-derived naïve B cells were cultured in the presence of IL-21 +TGF-β, IL-21 +APRIL or IL-21 +BAFF to induce class switch recombination to IgA. Regulatory B cell functions and phenotypes were assessed on the class switched IgA B cells. Results: We describe that APRIL promotes the differentiation of naïve human B cells to IL-10-producing IgA + B cells. These APRIL-induced IgA + B cells display a regulatory B cell phenotype and inhibit T cell and macrophage responses in vitro through expression of IL-10 and PD-L1. Moreover, APRIL-induced IL-10 producing regulatory B cells suppress inflammation in vivo in experimental autoimmune encephalitis (EAE) and contact hypersensitivity (CHS) models. Finally, we showed a strong correlation between APRIL and IL-10 in the inflamed synovial tissue of inflammatory arthritis patients. Conclusions: We identified a novel subset of regulatory B cells within the IgA switched B cell population that suppresses inflammation in vitro and in vivo, which indicate the potential relevance of this subset of B cells for immune homeostasis and immunopathology. Disclosure of Interest: C. Fehres: None declared, N. van Uden: None declared, N. Yeremenko: None declared, L. Fernandez: None declared, G. Franco Salinas: None declared, L. van Duivenvoorde: None declared, B. Huard: None declared, J. Morel: None declared, H. Spits Shareholder of: AIMM Therapeutics., M. Hahne: None declared, D. Baeten: None declared